(untitled) (Reflection and Critique Law Magazine, 2024)
This article aims to understand the reasons that lead the Police and the judiciary of the city of Santa Rita do Passa Quatro-SP, a small climatic resort 80 km from Ribeirão Preto-SP, to adopt police measures of condemnation, coercion, marginalization and indifference against an elderly lady, Dora, which generated national repercussions when she was arrested because her roosters were crowing. She intended to escape the pollution of the big city, and to live among fewer people, to have a new social life. Dora chooses the small town of Santa Rita do Passa Quatro-SP, a climatic resort with clean air, with just over 25 thousand inhabitants, which, despite being a large municipality geographically speaking, has a small urban area, when compared to other cities like Ribeirão Preto-SP, but has a large rural area composed of small farms and residencies. She acquires a small farm in the rural area and decides to make a space to raise roosters in her farm, which is also her home. She sets out to do it in the countryside, something she could never have done in the big city, roosters being the animals she most esteems; they could be dogs or cats. Foucault is remembered for his cat, as Dora will be for her roosters.